ADAPTATION STRATEGIES OF TRANSNATIONAL GRAIN TRADERS FACING GEOPOLITICAL SHOCKS AND FINANCIAL, LOGISTICS, INFRASTRUCTURE AND ENERGY CHALLENGES - TATARENKO, Nataliya; NABOK, Inna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The war in Ukraine, unleashed by the Russian Federation, has become an event of global political and economic scale – it has completely unbalanced the world economic system, jeopardized global food and energy security and created a number of other economic asymmetries. For Ukraine, whose economy has recently relied to great extent on the grain industry and grain trading, this has become a special test. Its development model has undergone significant transformations, and, first of all, the emphasis has shifted to the decisive role of the main institutions-actors that determine the fate of the national and world economy and their dynamics and stability. Using the example of the realization of Ukraine’s grain export potential in wartime, this study analyzes the role of transnational actors - grain traders, with an emphasis on the flexibility of their energy, logistical, financial and infrastructure strategies. The authors concluded that in the conditions of fierce confrontation between states, global imbalances in the food security system caused by the war stimulated the world community to find new ways to solve this problem. As a result, mechanisms of bilateral and multilateral economic diplomacy were activated and comprehensive political and economic support was provided to Ukraine. State support provided to producers and grain traders by Ukraine was also focused on ensuring world food security. However, the main effective actors in the negotiation process during the war are transnational grain and grain trading corporations, which, at the same time, used their economic potential to strengthen energy security, build new infrastructure, form financial networks in Ukraine, organize international logistics and a whole range of innovative strategies that were not inherent in them in the pre-war period. Corporate diplomacy and economic activity of transnational grain trading corporations was more effective than the political will of states and the world community. International grain traders have shown unprecedented resilience, transforming from pre-war models focused on minimizing costs to operations focused on risks and reservations. The new paradigm is based on multi-route reservations, dynamic contracting, strategic buffering in third countries and deep integration of geopolitical intelligence into daily trading decisions. The Ukrainian case has become a global benchmark for commodity trading in the context of a protracted military conflict and is already influencing corporate strategies in other vulnerable grain-exporting regions.